2016
DOI: 10.1016/j.chb.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between anhedonia and internet-related addictive behaviors in emerging adults

Abstract: Internet addiction (including online gaming) has been associated with depression. However, most prior research relating internet addiction symptomatology to depressive symptoms has been cross-sectional, conducted with children and adolescents, and only examined depressive symptoms as a broad construct. The purpose of the current study was to examine potential longitudinal associations between anhedonia (i.e., difficulty experiencing pleasure, a key facet of depression) and internet-related addictive behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…In other words, those studies that did not measure low mood separately from anhedonia may have concealed the relationship between anhedonia and video gaming. The current findings of this study are aligned with those of Guillot and colleagues [40], who found that anhedonia, assessed in college students, predicted greater compulsive Internet and addiction to video games nine to 18 months later. The present study replicated the finding in a younger, clinically referred sample.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In other words, those studies that did not measure low mood separately from anhedonia may have concealed the relationship between anhedonia and video gaming. The current findings of this study are aligned with those of Guillot and colleagues [40], who found that anhedonia, assessed in college students, predicted greater compulsive Internet and addiction to video games nine to 18 months later. The present study replicated the finding in a younger, clinically referred sample.…”
Section: Discussionsupporting
confidence: 90%
“…Converging evidence suggested that PVG is associated with externalizing symptoms, such as impulsivity [31], attention-deficit hyperactive disorder [31], and aggression and hostility [25,[32][33][34][35]. PVG is also associated with internalizing symptoms, such as depressive mood [36,37], social anxiety or social inhibition [11,38,39], anhedonia [40], and loneliness [34]. It appears that problematic video gaming is associated with many risk factors and associated features of mental health difficulties.…”
Section: Risk Factors In Problematic Video Gamingmentioning
confidence: 99%
“…This study sought to investigate the interplay between SNS addiction and IGD and how these two emerging technological addictions can uniquely and distinctively contribute to deterioration of psychological health in adolescents over and above the potential effects stemming from sociodemographic and technology-related variables. With regard to H1 (i.e., gender and age will contribute toward augmenting both SNS addiction and IGD symptoms ), this study was able to corroborate this hypothesis in relation to IGD, further supporting a large body of previous studies that found young age and male gender are key variables predicting IGD ( Cock et al., 2014 ; Guillot et al., 2016 ; Rehbein, Staudt, Hanslmaier, & Kliem, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, if by definition, the EMSs are stable and perpetuated over time, when patients with BAs experience emotional triggers, they will reactivate specific EMSs, and this will continue the vicious circle. Just as we said in the introduction, the EMSs are "comprised of memories, emotions, cognitions and bodily sensations regarding oneself and one's relationship with others, " it could be assumed that many alterations in cognition, in self-perceptions of emotions (i.e., alexithymia), and in the experience of pleasure (i.e., anhedonia), repeatedly reported in the literature among patients with BAs (Guillot et al, 2016;Moccia et al, 2017Moccia et al, , 2018, may be associated with the development and perpetuation of EMSs.…”
Section: Discussionmentioning
confidence: 99%